Implementation of behavior modification techniques for persons with mental disorders with low social skills (Case Study at Sentra Phalamartha Sukabumi, West Java, Indonesia) - Subardhini, Meiti; Sofiani, Tiara Tri; Hasbi, Syahla Julia (International Journal of Innovative Research and Scientific Studies, 2025)
Research on the application of behavior modification to improve social skills in mental disorders (PMD) at Sentra Phalamartha Sukabumi. Some of the techniques used are positive reinforcement, systematic desensitization, and other similar techniques based on different needs. An experimental Single Subject Design (SSD), including an A-B-A model, was used to assess intervention efficacy. The participants were two individuals with a deficiency in social skills — such as a healthy morning routine and periodic worship. The data gathering methods included observation, interviews, and Likert scale tests. Findings showed that the use of behavior modification methods was effective in improving the social skills of the participants. Maladaptive behavior was observed during the baseline, with an improvement following treatment. The intervention processes focused primarily on individuals and were positively effective at helping the subjects overcome their social hurdles. Interventions were conducted in the environment offered by Sentra Phalamartha. The outcomes of this study contribute to the establishment of micro and mezzo social work institutions and the utilization of behavior modification skills. It is anticipated that the results could serve as a reference for practitioners in social rehabilitation efforts to enhance the social function of persons with mental disorders based on their needs.